Effect of Iron Tailings and Slag Powders on Workability and Mechanical Properties of Concrete - Ruidong, Wu; Yu, Shen; Juanhong, Liu; Linian, Cheng; Guangtian, Zhang; Yueyue, Zhang (Frontiers in Materials, 2021)
Tailings are one of the largest solid wastes in stock at present. In order to improve the comprehensive utilization rate of tailings, especially to solve the difficult problems of the fine-grained tailings, the concrete composite admixture was prepared by using iron tailings powder and slag powder. In order to study the influence of iron tailings powder on the workability and long-term mechanical properties of concrete, C30 and C50 concrete with different iron tailings powder dosage were prepared, and the slump, expansion, flexural strength, splitting tensile strength and compressive strength of concrete at different ages were tested. The results show that the proper addition of iron tailing powder is beneficial to the working performance of concrete and can effectively reduce the time-loss of concrete fluidity.When the content of iron tailings powder in the composite admixture is 50%, the 1080d long age strength of C30 and C50 concrete can reach 50.3MPa and 80.7MPa. Based on the 28d compressive strength, the relative strength-age prediction model of iron tailings powder concrete was established. The calculation and experimental results show that the model can accurately predict the compressive strength of micro-powder concrete of iron tailings at long age, and the error rate is less than 1%. The results lay a theoretical foundation for the utilization of iron tailings in concrete.